Structural equation model of coping and life satisfaction of community-dwelling older people during the COVID-19 pandemic - Nasreen Lalani; Xu Dongjuan; Yun Cai; Greg W. Arling (SpringerOpen, 2023)
Abstract Background COVID-19 put older individuals at high risk for morbidity and mortality, isolation, reduced coping, and lower satisfaction with life. Many older adults experienced social isolation, fear, and anxiety. We hypothesized that successful coping with these stressors would maintain or improve satisfaction with life, a crucial psychological outcome during the pandemic. Our study investigated relationships between older people's coping and life satisfaction during the pandemic and their optimism, sense of mastery, closeness with spouse, family, and friends, and vulnerabilities from frailty, comorbid diseases, memory problems, and dependencies in instrumental activities of daily living (IADL). Methods The study was based on a special COVID-19 sample of 1351 community-dwelling older adults who participated in the 2020 Health and Retirement Survey. A comprehensive structural equation modeling was used to test direct and indirect effects, with life satisfaction as the main outcome and coping as a mediator between the other variables and coping. Results Most survey respondents were female and between the ages of 65-74 years. They averaged 1.7 chronic conditions, one in seven was frail, about one-third rated their memory as fair or poor, and about one in seven reported one or more difficulties in IADL. As hypothesized-older people with increased sense of mastery and optimism were better able to cope and had greater life satisfaction. In addition, close relationships with friends and with other family members besides the spouse/partner or children contributed to more successful coping, while the interpersonal closeness of all types contributed directly to greater life satisfaction. Finally, older people with more IADL limitations reported greater difficulty coping and lower life satisfaction, and those older people who were frail or had multiple comorbid diseases reported lower life satisfaction. Conclusions Optimism, sense of mastery and closeness with family/friends promotes coping and life satisfaction, whereas frailty and comorbidities make coping more challenging and lead to lower life satisfaction particularly during a pandemic. Our study improves on prior research because of its nationally representative sample and formal specification and testing of a comprehensive theoretical framework.